1974
DOI: 10.1111/j.1365-2362.1974.tb00419.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Acute Uraemia on Gluconeogenesis in Isolated Perfused Rat Livers

Abstract: Abetraet. The effect of acute uraemia on glucose and urea formation by isolated perfused liven of fasting rats was investigated.The basal gluconeogenesis following nephrectomy was significantly increased as compared to normal and sham operated controls. Enhanced glucose formation was associated with an increase in both urea synthesis and output of the p r l y metabolizable amino acids valine, leucine, and isoleucine. In the presence of a mixture of amino acids (serine, threonine, lysine, glutamic acid, ornithi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

1976
1976
1990
1990

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 26 publications
3
34
0
Order By: Relevance
“…In niormials, increased alaniniie delivery as providled by ani alaniniie inifutsion resuilts ini incereased alaninie levels (40). These finidings of' increased glutconeogeniesis lin atzoteinici miani correlate wvell with finin(iigs of increased in vitro hepatic gluiconeogeniesis in the urem-ic rat (12,13 (46) and( hepattic gluiconieogeniesis f'romi thiree carbon prectirsors (47). Whereas the eff'ect of' parathyroid hiormionc o)n adlenylate cyclase activity is less thian-the stiimutlation produtced by epiniephri ne o)r glutcagoni, parathyroid h-ormionie levels are suibstanltially elevated in chironiic renial f'ailuire (:36) andi( may' contributetc to the inicreased1 hiepatic gluiconieogemmesis.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In niormials, increased alaniniie delivery as providled by ani alaniniie inifutsion resuilts ini incereased alaninie levels (40). These finidings of' increased glutconeogeniesis lin atzoteinici miani correlate wvell with finin(iigs of increased in vitro hepatic gluiconeogeniesis in the urem-ic rat (12,13 (46) and( hepattic gluiconieogeniesis f'romi thiree carbon prectirsors (47). Whereas the eff'ect of' parathyroid hiormionc o)n adlenylate cyclase activity is less thian-the stiimutlation produtced by epiniephri ne o)r glutcagoni, parathyroid h-ormionie levels are suibstanltially elevated in chironiic renial f'ailuire (:36) andi( may' contributetc to the inicreased1 hiepatic gluiconieogemmesis.…”
Section: Discussionmentioning
confidence: 94%
“…Elevated rates of alanine formation and release may have been described in skeletal muscle of chronically uremic rats (11). Increased hepatic gluconeogenesis has been observed in the acutely uremic rat (12) and in rat liver slices ineuibated in serum obtained from uremic patients (13).…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest increased sensitivity to the gluconeogenic effects of glucagon in uremia. Increased amino acid incorporation into glucose has been observed in perfused rat livers after nephrectomy (42). It should be noted that while dialysis normalized the glucose response to glucagon (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Alanine and glutamine account for the bulk of amino acids released by muscle (21). Studies performed in vitro using an isolated perfused liver model for hepatic gluconeogenesis have demonstrated that uremia is associated with an increased maximal capacity for hepatic glucose production from amino acids (42,43). Because studies performed in vivo as well as in vitro have demonstrated that the rate of alanine delivery can be rate limiting for gluconeogenesis (7,44), the findings of the present study demonstrating an increased rate of alanine production and release from skeletal muscle in uremia, suggest that an increased rate of hepatic gluconeogenesis from alanine may indeed occur in vivo.…”
Section: Discussionmentioning
confidence: 99%